Central nervous system dysfunction and erythrocyte guanosine triphosphate depletion in purine nucleoside phosphorylase deficiency. Issue 4 (April 1987) - Simmonds, H A; Fairbanks, L D; Morris, G S; Morgan, G; Watson, A R; Timms, P; Singh, B
Abstract : Developmental retardation was a prominent clinical feature in six infants from three kindreds deficient in the enzyme purine nucleoside phosphorylase (PNP) and was present before development of T cell immunodeficiency. Guanosine triphosphate (GTP) depletion was noted in the erythrocytes of all surviving homozygotes and was of equivalent magnitude to that found in the Lesch-Nyhan syndrome (complete hypoxanthine-guanine phosphoribosyltransferase (HGPRT) deficiency). The similarity between the neurological complications in both disorders indicates that the two major clinical consequences of complete PNP deficiency have differing aetiologies: neurological effects resulting from deficiency of the PNP enzyme products, which are the substrates for HGPRT, leading to functional deficiency of this enzyme. immunodeficiency caused by accumulation of the PNP enzyme substrates, one of which, deoxyguanosine, is toxic to T cells. These studies show the need to consider PNP deficiency (suggested by the finding of hypouricaemia) in patients with neurological dysfunction, as well as in T cell immunodeficiency. They suggest an important role for GTP in normal central nervous system function.